Metodología para el control de gestión en la empresa Feve Pasta de la ciudad de Portoviejo - Muñoz Cusme, Génesis Belén (2021)
The objective of this degree work was to propose a methodology for the management control of the FEVE PASTA company that contributes to the alignment of its results with the strategic organizational objectives. A bibliographic, field, exploratory and descriptive research was applied, which made it possible to collect the necessary information for the development of the research. The research procedure was developed in three phases, the initial one was to diagnose the current situation of the FEVE PASTA company in relation to strategic planning and management control where different tools and techniques were used such as the survey, interview, observation, traffic light Delphi and statistics, through questionnaire, strategy map and early warning system. The second phase made it possible to determine the management control methodology that fits the characteristics of the company, with the help of a panel of experts. In the third phase, we proceeded to determine the contribution of the proposed methodology for this, a system of indicators focused on the Balanced Scorecard and supported by traffic lights was structured, a technique that allowed visualizing the situation of the company at the end of the second semester of 2020 It was possible to determine that in the studied company, there are financial indicators that have shown a behavior within the projected values, but even so there are weaknesses that must be improved through the timely and early application of strategies that can improve economic profitability and projection. of the company in the future.